Formulation of a Cream Preparation From Areca Nut Seed (Areca Catechu) And Pineapple Stump (Ananas Comosus) as A Scar Remover - Lubis, Afrina Dewi; Dongoran, Rini; Diningsih, Ayus (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2023)
This study aims to formulate and evaluate a topical cream preparation based on areca nut seed (Areca catechu) and pineapple stump (Ananas comosus) extracts as a scar-removing agent. Areca nut seeds contain tannins and flavonoids, which act as antioxidants, while pineapple stumps contain bromelain, an enzyme with proteolytic and anti-inflammatory properties. These ingredients were selected for their ability to accelerate wound healing and stimulate the regeneration of damaged skin tissue. The cream formulation was prepared by incorporating areca nut seed and pineapple stump extracts into a cream base using a hot emulsification method. The resulting cream was then physically tested for homogeneity, viscosity, spreadability, pH, and stability at room temperature and accelerated conditions over a 30-day period. Additionally, an in vivo test was conducted on male rats with incisions on the dorsal area to assess the cream’s effectiveness in accelerating wound healing and reducing scar formation. The findings indicate that the formulated cream has good physical stability, high homogeneity, suitable viscosity for topical use, optimal spreadability, and a skin-safe pH. The in vivo test showed that rats treated with the areca nut and pineapple stump cream experienced faster wound healing compared to the control group. Histopathological analysis revealed increased epithelial tissue regeneration and reduced scar tissue formation. Thus, the cream formulation from areca nut seeds and pineapple stump has the potential to be developed as an effective natural product for scar treatment. This product provides a safer and more environmentally friendly alternative to the synthetic chemical-based products commonly available on the market.